Quantitative T1 and proton density mapping with direct calculation of radiofrequency coil transmit and receive profiles from two‐point variable flip angle data. (12th January 2016) - Baudrexel, Simon; Reitz, Sarah C.; Hof, Stephanie; Gracien, René‐Maxime; Fleischer, Vinzenz; Zimmermann, Hilga; Droby, Amgad; Klein, Johannes C.; Deichmann, Ralf
Abstract : Quantitative T 1 mapping of brain tissue is frequently based on the variable flip angle (VFA) method, acquiring spoiled gradient echo (GE) datasets at different excitation angles. However, accurate T 1 calculation requires a knowledge of the sensitivity profile B 1 of the radiofrequency (RF) transmit coil. For an additional derivation of proton density (PD) maps, the receive coil sensitivity profile (RP) must also be known. Mapping of B 1 and RP increases the experiment duration, which may be critical when investigating patients. In this work, a method is presented for the direct calculation of B 1 and RP from VFA data. Thus, quantitative maps of T 1, PD, B 1 and RP can be obtained from only two spoiled GE datasets. The method is based on: (1) the exploitation of the linear relationship between 1/PD and 1/ T 1 in brain tissue and (2) the assumption of smoothly varying B 1 and RP, so that a large number of data points can be fitted across small volume elements where B 1 and RP are approximately constant. The method is tested and optimized on healthy subjects. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A method is described which allows us to obtain the RF coil transmit ( B 1 ) and receive (RP) sensitivity profiles directly from two‐point variable flip angle (VFA) data without the requirement for additional measurements. It is based on: (1) an exploitation of the linear relationship between 1/ T 1 and 1/PD (proton density) in brain tissue (Fatouros' approximation); and (2) the assumption of smoothly varying B 1 and RP profiles. Average deviations between calculated and reference B 1 and RP maps amounted to 3–4%.